New directions in educational ethnography - Hopson, Rodney K. (Rodney Kofi); Kaul, Akashi; Rodick, William (Bingley : Emerald Group Publishing Limited, 2016)
Volume 13 relaunches the book series after a 9-year hiatus and addresses new directions in the field of educational ethnography. The authors in the book share methodological similarities, but their applications, contexts, treatments, and contributions to the field as evidenced here are unique and vary considerably. The diversity of views and perspectives of ethnographic theory and method in educational settings are on full display, from the street to urban and suburban classrooms and to college settings, where gender, race, class, and power dynamics impact learners, teachers, parents, and communities. Taken together, the chapters reinvigorate and redirect a new set of possibilities and opportunities in ethnographic research, while highlighting shifts, problems and new directions for the field.
Prelims -- Introduction: new directions in educational ethnography: shifts, problems, and reconstruction -- Against all odds: the ethnography of hope among Haitian youth in difficult circumstances -- Using queer theory to read the hushing of boys reading: "a thought of a method" of queer educational ethnography -- Where machines rant, recite poems, and take outrageous selfies: an ethnography of a teachers' facebook group -- Relying on local contexts to foster and thwart black student academic success: an ethnographic account of teachers fostering academic success for (some) black students -- The emergence of critical presence ethnography: capturing the ripples of self in educational contexts -- (critical) educational ethnography: methodological premise and pedagogical objectives -- A critical ethnographic approach to transforming norms of whiteness in marginalized parents engagement and activism in schools -- Ethnography as subject, ethnography as object: experimenting with research in a college writing classroom -- Teaching through discussion: a mixed qualitative methods study of educator facilitation practices in a small group learning context using ethnographic and conversation analytic approaches -- About the authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Anthropology -- Cultural & Social; Sociology; Educational anthropology; Multicultural education